Viewing Skill in 7th Grade English for Nusantara Student’s Book: An Analysis of Strategy - Pratiwi, Nabila Yuditya; Nugraheni, Dyah; Hawa, Faiza (Melati Institute, 2024)
Nowadays Kurikulum Merdeka is the most recent curriculum to be used in Indonesia, which in accordance with the decision of the Head of the Educational Standards, Curriculum and Assessment Agency of the Ministry of Education, Culture, Research and Technology Number 008/H/Kr/2022, emphasizes literacy skills. This study aims on two objectives, there are to find the types of viewing skills and to find the viewing skills process in 7th grade English for Nusantara student’s book. The design of the study uses descriptive qualitative research design, which the researcher implements documentation method to collect the data with variables in the 7th grade English for Nusantara student’s book. The researcher analyzes that 7th grade English for Nusantara student’s book is contained with two types of viewing skill, namely visual literacy and critical viewing. This study also found that there are three stages of viewing skill process namely pre-viewing, during viewing, and post-viewing. This study is expected to add knowledge in implementation of viewing skill for teacher and students during teaching and learning process, and the next researchers who will conduct a research of viewing skill in wider point of view.